The opioid methadone induces a local anaesthetic‐like inhibition of the cardiac Na+ channel, Nav1.5. (January 2014) - Schulze, V; Stoetzer, C; O'Reilly, A O; Eberhardt, E; Foadi, N; Ahrens, J; Wegner, F; Lampert, A; de la, J; Leffler, A
<x xml:space="preserve">Abstract</x> Background and Purpose Treatment with methadone is associated with severe cardiac arrhythmias, a side effect that seems to result from an inhibition of cardiac hERG K+ channels. However, several other opioids are inhibitors of voltage‐gated Na+ channels. Considering the common assumption that an inhibition of the cardiac Na+ channel Nav1.5, is the primary mechanism for local anaesthetic (LA)‐induced cardiotoxicity, we hypothesized that methadone has LA‐like properties leading to a modulation of Nav1.5 channels. Experimental Approach The whole‐cell patch clamp technique was applied to investigate the effects of methadone on wild‐type and mutant human Nav1.5 channels expressed in HEK293 cells. A homology model of human Nav1.5 channels was used to perform automated ligand‐docking studies. Key Results Methadone inhibited Nav1.5 channels in a state‐dependent manner, that is, tonic block was stronger with inactivated channels than with resting channels and a use‐dependent block at 10 Hz. Methadone induced a concentration‐dependent shift of the voltage dependency of both fast and slow inactivation towards more hyperpolarized potentials, and impaired recovery from fast and slow inactivation. The LA‐insensitive mutants N406K and F1760A exhibited reduced tonic and use‐dependent block by methadone, and docking predictions positioned methadone in a cavity that was delimited by the residue F1760. Dextromethadone and levomethadone induced discrete stereo‐selective effects on Nav1.5 channels. Conclusions and Implications Methadone interacted with the LA‐binding site to inhibit Nav1.5 channels. Our data suggest that these channels are a hitherto unrecognized molecular component contributing to cardiac arrhythmias induced by methadone.